Multisystem Inflammatory Syndrome Temporally Related to COVID-19 in Children From Latin America and the Caribbean Region: A Systematic Review With a Meta-Analysis of Data From Regional Surveillance Systems - Ruvinsky, Silvina; Voto, Carla; Roel, Macarena; Fustiñana, Ana; Veliz, Natalia; Brizuela, Martin; Rodriguez, Susana; Ulloa-Gutierrez, Rolando; Bardach, Ariel (Frontiers in Pediatrics, 2022)
Background: With the emergence of the COVID-19 pandemic, increasing numbers of cases of the multisystem inflammatory syndrome in children (MIS-C) have been reported worldwide; however, it is unclear whether this syndrome has a differential pattern in children from Latin America and the Caribbean (LAC). We conducted a systematic review and meta-analysis to analyze the epidemiological, clinical, and outcome characteristics of patients with MIS-C in LAC countries. Methods: A systematic literature search was conducted in the main electronic databases and scientific meetings from March 1, 2020, to June 30, 2021. Available reports on epidemiological surveillance of countries in the region during the same period were analyzed. Results: Of the 464 relevant studies identified, 23 were included with 592 patients with MIS- C from LAC. Mean age was 6.6 years (IQR, 6-7.4 years); 60% were male. The most common clinical manifestations were fever, rash, and conjunctival injection; 59% showed Kawasaki disease. Pool proportion of shock was 52%. A total of 47% of patients were admitted to the pediatric intensive care unit (PICU), 23% required mechanical ventilation, and 74% required vasoactive drugs. Intravenous gamma globulin alone was administered in 87% of patients, and in combination with steroids in 60% of cases. Length of hospital stay was 10 days (IQR, 9-10) and PICU stay 5.75 (IQR, 5-6). Overall case fatality ratio was 4% and for those hospitalized and in the PICU it was 7%. Conclusion: Limited information was available on the clinical outcomes. Improvements in the surveillance system are required to obtain a better epidemiologic overview in the region. Conclusion: Limited information was available on the clinical outcomes. Improvements in the surveillance system are required to obtain a better epidemiologic overview in the region.